Thermal properties of Pr2/3Sr1/3MnO3 manganites:PdO composites. (October 2017) - Rao, Ashok; Manjunatha, S.O.; Bhatt, Ramesh Chandra; Awana, V.P.S.; Lin, C.F.; Kuo, Y.K.; Poornesh, P.
Abstract: In the present communication the results on thermal conductivity, Seebeck coefficient and specific heat of Pr2/3 Sr1/3 MnO3 :PdO composites are reported. All the samples exhibit a pronounced anomaly in thermal conductivity ( κ ) at their respective Curie temperatures, T C of the samples. It is also observed that the overall magnitude of κ decreases with increasing Pd content. The observed reduction of the total k ( T ) is discussed with various thermal scattering mechanisms. The temperature-dependent Seebeck coefficient data S ( T ) in the high temperature region is analyzed within the framework of Mott's polaron hopping model. The analysis of low-temperature S ( T ) data reveals that the electron-magnon scattering contribution dominates the thermoelectric transport at low temperatures. The magnetic contribution for the C P and change in entropy (Δ S ) during the magnetic phase transition is also evaluated. Highlights: Thermal conductivity deceases with increase in Pd content. Electron-magnon scattering dominates the thermoelectric transport at low temperatures. Mott's polaron hopping mechanism is operative at high temperatures.